THE CREATION OF “REPURPOSING” CERAMIC USING ROOF TILES WASTE - Aries Budi Marwanto; Johan Ies Wahyudi; Raden Ersnathan Budi Prasetyo (ARTISTIC : International Journal of Creation and Innovation, 2022)
There was a lot of used roof tile discovered throughout the village. However, the community did not turn it into usable items. The roof tile waste motivated us  to turn it into artwork. This artistic research focused on the production of repurposing ceramic pieces utilizing roof tile waste materials. This creative study made use of the experimentation, reflection, and formation phases of Dharsono's artistic creation approach. This artistic creation process resulted in a jug of art entitled "Wanawarih." This artwork is full of symbolic expression values about the trilogy of vitality, namely forest preservation, water function maintenance, and earth manifestation